A Case Study on SEWA Ecotourism (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Shree Vanalakshmi GaneshpuraMahila Sewa  VrukshUtpadakSahkari Mandli Ltd, created  with the intention to provide employment to  marginal womeninGaneshpura village, situated  in the Mehsana district of Gujarat, is now an  Eco-Tourism center too. It started with 41  women, who transformedbarren 10-acre land  into an irrigated plot growing various fruits,  vegetables, various types of ayurvedic plants,  trees, etc. The entire model is unique in nature  supporting the self-reliance of these SEWA  sisters. The visitors enjoy its beauty, nature,  Gujarati food, culture, organic fruits and  vegetables,and the peace of this place.
Keywords: Ecopreneurs; Ecotourism; Employment; Rural; SEWA